Point-surveillance of antibiotic resistance in Enterobacteriaceae isolates from patients in a Lagos Teaching Hospital, Nigeria - Muhabat Adeola Raji; Wafaa Jamal; Omoh Ojemhen; Vincent O. Rotimi (Elsevier, 2013)
Summary: Objectives: This study was carried out to determine a point prevalence of drug resistance and extended-spectrum β-lactamase (ESBL) among members of the family Enterobacteriaceae. Methods: Consecutive clinically significant non-repetitive isolates obtained from both hospitalized patients and outpatients' samples were studied. The isolates were identified using VITEK 2 while susceptibility testing was performed against 16 antibiotics using the E-test strips. Phenotypic production of ESBL was detected by E-test ESBL method. Positive isolates were confirmed by PCR. Results: Of a total of 102 isolates studied, 43 (42.2%) were Escherichia coli and 32 (31.4%) Klebsiella pneumoniae. These isolates demonstrated remarkable high rates of resistance to the β-lactam antibiotics, except the carbapenems and piperacillin-tazobactam. Fifty-two (51%) were resistant to ≥3 classes of drugs and 29 (28.4%) to ≥5 drugs. Thirty-eight (37.3%) were ESBL producers. Of these, 21 (55.3%) were E. coli and 12 (31.6%) K. pneumoniae. Thus, the overall prevalence of ESBL-producing E. coli was 20.6% and K. pneumoniae 11.8%. Conclusions: This study showed an alarmingly high prevalence of antibiotic resistance in invasive Enterobacteriaceae isolates and a high prevalence of ESBL producers in the study center. Antibiotic stewardship and other preventive strategies are recommended to reduce the high rate of resistant bacteria in this hospital. Keywords: Antibiotic resistance, ESBL, Enterobacteriaceae, Lagos, Nigeria